2021
DOI: 10.21203/rs.3.rs-1139760/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility Studies on Treatment of Household Greywater Using Phytoremediation Plants

Abstract: Recycling and reusing of wastewater acquired high priority among the research community to meet the ever-increasing demand for groundwater, and to tackle water scarcity in every country. In this scenario, a grey water treatment system is developed with a vertical flow wetland construction tank (VFWCT)with sand, gravel and silex as media combined with phytoremediation technology using plants like Cyperus rotundus, Canna indica, Typha angustifolia, Cyperus pangorei, and Phragmites australis. The assessment param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The pollutant removal efficiency depends on their oxygen and nutrient concentration, temperature, pH and other abiotic factors [41,42]. Studies have demonstrated that the organic pollutants' removal efficiency by phytoremediation is about 56% [43]. Tagetes patula and Pisum sativum have been selected due to their excellent adsorption properties and their phytoremediation capacities [44,45].…”
Section: Methodsmentioning
confidence: 99%
“…The pollutant removal efficiency depends on their oxygen and nutrient concentration, temperature, pH and other abiotic factors [41,42]. Studies have demonstrated that the organic pollutants' removal efficiency by phytoremediation is about 56% [43]. Tagetes patula and Pisum sativum have been selected due to their excellent adsorption properties and their phytoremediation capacities [44,45].…”
Section: Methodsmentioning
confidence: 99%
“…The pollutants removal efficiency depends on oxygen and nutrient concentration, temperature, pH and other abiotic factors [39,40]. Studies present the organic pollutants removal efficiency by plants is about 56.56% and 50.25% [41]. Tagetes patula and Pisum sativum have been selected according their excellent adsorption properties and their phytoremediation capacities to retain organic pollutants [42,43].…”
Section: Methodsmentioning
confidence: 99%